Mechanical properties study of VO2 micro‐beam according to metal‐insulator transition. Issue 8 (28th April 2021) - Kim, Youngho; Cho, Hyeon Ho; Bae, Ji Kwon; Lee, Jaeyeong; Lee, Sang Hoon; Dong, Xue; Asghar, Ghulam; Choi, Jae‐Young; Yu, Hak Ki
Abstract: Many attempts have been made to develop applications using the metal‐insulator transition (MIT) phenomenon of VO2 . However, the difference in the densities of the two phases poses serious obstacle for those applications, as it can destroy or disable during the phase transformations. For microsized or nanosized devices, this aspect can be critical. We attempted to measure the mechanical properties when the two phases co‐exist, as well as for an individual phase, via in‐situ control of the temperature of plate‐shaped VO2 . The lamella structure is formed during MIT. At this time, the stress is applied by the gradient of density, and the residual strain can easily occur at the interface of each phase. Therefore, the co‐exist state was judged to be the most vulnerable during the MIT. The change in mechanical properties of VO2 during phase transition was also simulated by finite element method.